Preventive Measures for the Impacts of Social Media Networks in Security and Privacy - A Review - Vivekanandam, B.; Midhunchakkaravarthy, (Journal of ISMAC, 2022)
Recently, smartphones have made it simpler than ever, to access social networking sites, which have become an integral part of our daily lives. However, safety and privacy are still major concerns. User-shared material, such as images, movies, and audio recordings may provide several safety and privacy concerns. Especially when the user uploads sensitive content, the attacker has the ability to misuse the information. If minors are targeted, the dangers are significantly greater. This study examines how data breaches or leaks impact the community and how security and privacy are compromised. Administrative authority, private service keys, private employee information, and publicly available databases have all been reported to be subjected to mass data leak. This study investigates the potential dangers, steps to avoid them, and remedies that could be found. Finally, this study provides merits and demerits of using social network sites through modern threat cases. Numerous case studies have been carried out to understand what may go wrong with online social networks.
Keywords: Network security; social media; preventive measure; modern threat; phishing